Wudhu as Spiritual Therapy: A Thematic Study of Verses and Hadiths on the Purity of the Soul in Strengthening Spiritual Literacy - Jailani, Ali Muddin (Journal of Practice Learning and Educational Development, 2026)
This study discusses wudu as a form of spiritual therapy that not only serves as a prerequisite for worship but also holds profound psychological and theological significance. In Islamic teachings, wudu is understood as a process of physical and spiritual purification that prepares a Muslim to worship and draw closer to Allah Almighty. Using a thematic exegesis (tafsir maudhu‘i) approach to analyze Qur’anic verses and the Prophet Muhammad’s hadiths, this research reveals that each act in wudu carries symbolic meaning related to self-purification and self-control. Verses such as QS. Al-Baqarah [2]: 222 and prophetic traditions on wudu indicate that physical cleanliness reflects inner purity, which fosters spiritual tranquility. The findings show that wudu embodies three essential dimensions: the ritual dimension as an act of obedience to Islamic law, the psychological dimension as a medium for relaxation and emotional calmness, and the spiritual dimension as a means of inner healing that connects humans with their Creator. Psychologically, the practice of wudu has been shown to reduce stress levels, enhance focus, and strengthen emotional balance through stimulation of the body’s nervous system. Theologically, wudu is part of the process of tazkiyah al-nafs (purification of the soul), shaping a Muslim’s character to be pure, peaceful, and spiritually aware. Therefore, wudu is not merely a ritual of physical cleanliness but also a form of spiritual healing that restores harmony between body, mind, and soul.